EKOSISTEM LITERASI SASTRA ANAK DI SEKOLAH DASAR MARABAHAN (CHILDREN'S LITERACY ECOSYSTEM AT MARABAHAN ELEMENTARY SCHOOL) - Novitasari, Aulia (Universitas Lambung Mangkurat, 2024)
AbstractChildren's Literacy Ecosystem at Marabahan Elementary School. Learning literature in elementary schools can be seen in the Indonesian language subject. Learning literature in elementary schools uses children's literature. The teacher plays an important role in selecting the appropriate and suitable children's literature in accordance with children’s development and needs as readers. This selection is based on certain criteria. Besides teachers, students can also provide responses to learning literature at school. This study aims to describe the children's literature used in Marabahan elementary school and the selection criteria by teachers. This study also describes the results of children's responses to children's literature used in learning. The results of the children’s responses concern the teacher's choice of children's literature based on the point of view of the child reader. Used a qualitative approach with an analytic descriptive method. The data sources were informants and respondents. Data were collected from observations, interviews, and questionnaires. Data analysis covered data reduction, presentation, and drawing conclusions. The results showed that first, the types of children's literature used by the teacher were fables, fairy tales, legends, and folktales. Second, the criteria used in the selection of children's literature used were interesting stories, length of stories, the content of moral values, age appropriateness, familiar stories, rich in values, and cultural insertion in the stories. Third, the children's responses showed positive results in assessing the children's literature. Social factors affecting their responses were student background, teacher background, teacher stimulus, library conditions, and textbooks used.Keywords: literacy ecosystem, children's literature, children's readers, learning literatureAbstrakEkosistem Literasi Sastra Anak di Sekolah Dasar Marabahan. Pembelajaran sastra di sekolah dasar tertuang pada mata pelajaran Bahasa Indonesia. Pembelajaran sastra di sekolah dasar menggunakan sastra anak dalam pembelajaran. Sikap selektif diperlukan dalam pemilihan sastra anak disesuaikan dengan perkembangan dan kebutuhan pembaca anak. Guru memiliki peranan dalam memilih sastra anak yang tepat untuk digunakan dalam pembelajaran. Pemilihan didasari kriteria yang ditetapkan oleh guru. Siswa akan memberikan respons dan tanggapan terhadap pembelajaran sastra yang diajarkan oleh guru di sekolah. Penelitian ini bertujuan mendeskripsikan sastra anak yang digunakan di sekolah dasar Marabahan beserta kriteria pemilihan sastra anak oleh guru. Penelitian ini juga mendeskripsikan hasil respons pembaca anak terhadap karya sastra anak yang digunakan dalam pembelajaran sastra. Hasil respons pembaca anak akan mengamati bagaimana sastra anak pilihan guru dalam sudut pandang siswa. Penelitian ini menggunakan pendekatan kualitatif dengan metode deskriptif analitik. Sumber data penelitian berupa informan dan responden. Teknik pengumpulan data dilakukan dengan observasi, wawancara, dan angket. Teknik analisis data melalui reduksi data, penyajian data, dan penarikan simpulan. Hasil penelitian menunjukkan bahwa, pertama, jenis sastra anak yang digunakan guru yakni fabel, dongeng, legenda, dan cerita rakyat. Kedua, kriteria yang digunakan guru dalam pemilihan sastra anak cerita menarik, panjang cerita, nilai moral, usia, cerita familiar, kandungan nilai, dan pengenalan budaya. Ketiga, respons pembaca anak menunjukkan hasil yang positif dalam menilai sastra anak yang dipilih oleh guru. Faktor sosial yang mempengaruhi respons pembaca anak yaitu latar belakang siswa dan guru, stimulus guru, kondisi perpustakaan, dan buku teks yang digunakan.Kata Kunci: ekosistem literasi, sastra anak, pembaca anak, pembelajaran sastra